Pengaruh Motivasi Belajar dan Kecerdasan Emosi terhadap Disiplin Mahasiswa FKIP Umtas - Resti Fauzi Lestari; Nandhini Hudha Anggarasari; Maesaroh Lubis (Medan Resource Center, 2022)
The progress of a country can be seen from the quality of human resources, forming quality humans, of course, cannot be done in an instant and spontaneous way, but can be done through education. high emotional intelligence too. The purpose of this study was to determine (1) is there an influence of learning motivation on discipline (2) is there an influence of emotional intelligence on discipline (3) is there an influence of learning motivation and emotional intelligence on the discipline of FKIP students, Muhammadiyah University of Tasikmalaya. This research is an ex-post facto research with a research population of 970 with a sample of 283 students from the Faculty of Teacher Training and Education, University of Muhammadiyah Tasikmalaya using proportionate random sampling. The sample selection used the sample probability technique, the instrument testing was carried out on students outside the sample as many as 48 students, data collection used a questionnaire method and the techniques used were descriptive techniques and multiple regression analysis techniques. The results of this study are: (1) the level of learning motivation is included in the medium category, (2) the level of emotional intelligence is included in the medium category and (3) the level of discipline is included in the medium category (4) there is an influence between learning motivation on student discipline and the value of tcount 3,025 and ttable 1,968 (5) there is an influence between emotional intelligence on student discipline with a tcount of 4.723 and ttable of 1,968 (6) there is a mutual influence between learning motivation and emotional intelligence on student discipline.